Molecular evaluation of Ehrlichia chaffeensis - Sirigireddy, Kamesh Reddy (Kansas State University, 2008)
Ehrlichia chaffeensis, an emerging tick-borne pathogen, causes human monocytic ehrlichiosis (HME). The relationship between E. chaffeensis and its target cells in ticks and vertebrates is critical as the organism must persist in them. We hypothesize that E. chaffeensis alters gene expression in support of adapting to dual hosts. In support of testing this hypothesis, we developed an ORF-based microarray and performed global transcriptional analysis on the pathogen grown in macrophage and tick cells. The analysis revealed the expression of about 30% of all the predicted E. chaffeensis genes, in macrophages or tick cell. Two-thirds of the transcribed genes are common for both host cell backgrounds. About 20% of the commonly expressed genes also varied in expression levels which ranged from two to five fold. Microarray data was verified by RT-PCR for a subset of randomly selected genes. Together, this is the first report describing the global host cell-specific gene expression patterns in E. chaffeensis. Differential gene expression may be an important adaptive mechanism used by E. chaffeensis for its continued survival in dual hosts. To test this hypothesis, we established many basic protocols and tools needed for performing mutational analysis in E. chaffeensis. Four antibiotic selection markers; gentamicin, chloramphenicol, spectinomycin and rifampin, and two promoters constitutively expressed in E. chaffeensis, genes rpsL and tr, were identified. Two regions of the genome were also identified for performing initial mutational analysis. Several plasmid constructs were also made. The optimal conditions for introducing these plasmids into host cell-free viable E. chaffeensis organisms were also established. The molecular evaluation of several E. chaffeensis transformants using these plasmids suggested that the plasmids gained entry, but failed to get integrated into the genome or remain in the bacteria for longer periods of time. In summary, we demonstrated global host cell-specific differential gene expression in E. chaffeensis by employing microarray analysis. Numerous host-specific expressed genes will be important for studies leading to effective methods of control. We also established several basic protocols and tools needed for performing mutational analysis useful in evaluating the impact of the loss of expression of uniquely expressed genes.
Keywords: Ehrlichia chaffeensis; Microarray; Genetic Manipulation; Gene expression; Biology, Microbiology (0410); Biology, Molecular (0307); Biology, Veterinary Science (0778)